Tax revenue inefficiency and political risk factors: The Hen or The egg? - Agumas Alamirew Mebratu (Cogent Business & Management)
Better tax administration and revenue mobilization can increase tax revenue performance while also strengthening the connection between the state, the business sector, and civil society. Despite efforts over the previous two decades, the ratio of tax receipts to GDP and tax effort in Sub-Saharan Africa remains low when compared to OECD nations. This is due to inefficient tax revenue collection. As a result, the primary objective of this study was to investigate experimentally the sources of tax revenue inefficiency in Sub-Saharan African nations between 2000 and 2021 using a secondary data set and half-normal, exponential-normal, and truncated-normal estimate techniques. According to the empirical findings, tax revenue inefficiency has a positive and significant relationship with corruption, democratic accountability, law and order, and religious tensions, and it has a negative and significant relationship with bureaucratic quality, internal conflict, government stability, and military in politics. The study concludes that, depending on the estimating approach used, political risk variables have a significant impact on tax revenue inefficiencies. Before formulating tax policy, tax policy makers shall first determine the extent of tax revenue inefficiencies.